THE CONTRIBUTION OF ECOLOGICAL PSYCHOLOGY TO MORAL DEVELOPMENT. A STUDY WITH ADOLESCENTS - Cortés Pascual, Alejandra (Anales de Psicología / Annals of Psychology, 2002)
The awareness and knowledge about the value patterns in adolescents is an important aspect to understand their moral development. The moral theory of Kohlberg, based on a evolutionary- cognitive approach, has been and still is a perspective from which this field can be investigated. This approach presents some limitations though, and that is why it is attempted to connect this Kohlbergian theory with the ecology of Bronfenbrenner, which has a culturalist focus. The goal is to understand integrally the moral development, and specifically the value patterns of young people. Both theories are a suitable framework to analyse themoral development of the subjects within a certain context. To implement this idea a research was carried out to discover the dilemmas, the moral values and the level of reasoning of adolescents in relation to the theories of Kohlberg and Bronfenbrenner. The theoretical evaluation and the empirical conclusions of this investigation lead to psycho-evolutionary approaches and possible intervention strategies.